5x-2(4x-12)=-7x-12

Simple and best practice solution for 5x-2(4x-12)=-7x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2(4x-12)=-7x-12 equation:


Simplifying
5x + -2(4x + -12) = -7x + -12

Reorder the terms:
5x + -2(-12 + 4x) = -7x + -12
5x + (-12 * -2 + 4x * -2) = -7x + -12
5x + (24 + -8x) = -7x + -12

Reorder the terms:
24 + 5x + -8x = -7x + -12

Combine like terms: 5x + -8x = -3x
24 + -3x = -7x + -12

Reorder the terms:
24 + -3x = -12 + -7x

Solving
24 + -3x = -12 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
24 + -3x + 7x = -12 + -7x + 7x

Combine like terms: -3x + 7x = 4x
24 + 4x = -12 + -7x + 7x

Combine like terms: -7x + 7x = 0
24 + 4x = -12 + 0
24 + 4x = -12

Add '-24' to each side of the equation.
24 + -24 + 4x = -12 + -24

Combine like terms: 24 + -24 = 0
0 + 4x = -12 + -24
4x = -12 + -24

Combine like terms: -12 + -24 = -36
4x = -36

Divide each side by '4'.
x = -9

Simplifying
x = -9

See similar equations:

| 41/82 | | 20-15=17 | | M/11=11 | | 32/x=2 | | 1/4(8x=20)=11 | | 2x^2-3x-8= | | 54=4x-10 | | 3+2=21 | | y-32=-4(x+5) | | x2=8/125 | | 7.056/5.88 | | x-0.05x=23.74 | | 1/3x-9=1/2x-6-5/6 | | 3.2+8.4x+9.33=6.2x-4.2 | | -44=4x-4 | | X-3/1/8=5/12 | | 4(x-2)=-3(x+4)-10 | | 2.058/5.88 | | x+y=2x+y | | 15ab+9a=0 | | X(2x+1)=6 | | 2.058/588 | | 8sin^2x-5sinx-2=0 | | 8-6(2x-9)=60 | | 250/10 | | 45-(-86)=z | | 3x-2=10x+5 | | 6c-12+3c=12 | | x-(x*0.05)=23.74 | | -900=10x | | 20/.5 | | -9(-4+5n)-(-16n+18)= |

Equations solver categories